Pengembangan Bahan Ajar Matematika Menggunakan Model Problem Based Learning (PBL) Terhadap Minat Belajar Siswa di Kelas IV Sekolah Dasar - Ahmad Landong; Alviona Alviona; Siti Fadlina Ningrum; May Liavani (Jurnal Dirosah Islamiyah, 2023)
The development of increasingly modern times, teachers are required to innovate regarding learning media. This study aims to develop Mathematics teaching materials using the Problem Based Learning model in class IV SD. The subjects of this study were media experts, material experts, learning experts and fourth grade students at SD Negeri 101998 Silinda. The research method used is the research and development method or R&D. The research model used in this study is 4D, namely: Define, Design, Development and Disseminate. The data collection technique in this study was a questionnaire using a Likert scale. Based on the questionnaire assessment of the trial, the score of the teacher response product trial was obtained with an assessment result of 4.5 so that it was included in the 4.20 ≤ N ≤ 5.00 category: with "very good" quality and the results of the student response trial assessment were 4, 54 fall into the "very good" category. Keywords: Teaching materials, PBL, Mathematics